Overexpression of Ginkgo biloba Hydroxy-2-methyl-2-(E)-butenyl 4-diphosphate reductase 2 gene (GbHDR2) in Nicotiana tabacum cv. Xanthi - Kim, Yeon Bok; Kim, Sang-Min; Sathasivam, Ramaraj; Kim, Yong-Kyoung; Park, Sang Un; Kim, Soo-Un (SPRINGER HEIDELBERG, 2021)
2-C-Methyl-d-erythrol-4-phosphate (MEP) pathway in plant supplies isoprene building blocks for carotenoids and chlorophylls essential in photosynthesis as well as plant hormones such as gibberellin and abscisic acid. To assess the effect of overexpression of the terminal enzyme of the MEP pathway, 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate reductase (HDR), transgenic Nicotiana tabacum overexpressing class 2 HDR from Ginkgo biloba (GbHDR2) under the control of 35S promoter was constructed. Contents of chlorophylls a and b in transgenic tobacco were enhanced by 19 and 7%, respectively, compared to those of the wild type. The carotenoid level was also 18% higher than that in the control plant. As a result, photosynthetic rate of the transgenic tobacco was increased by up to 51%. Diterepenoid duvatrienediol content of transgenic tobacco was also elevated by at least sixfold. To explore the molecular basis of the enhanced isoprenoid accumulation, transcript levels of the key genes involved in the isoprenoid biosynthesis were measured. Transcript levels of geranylgeranyl diphosphate synthase (GGPP), kaurene synthase (KS), gibberellic acid 20 oxidase (GA20ox), and phytoene desaturase (PD) genes in the transgenic tobacco leaves were about twofold higher compared to the wild type. Therefore, upregulation of down-stream genes involved in biosynthesis of di- and tetraterpenoids due to GbHDR2 overexpression was responsible for elevated production of isoprenoids and enhanced photosynthetic rate.
Keywords: 1-DEOXY-D-XYLULOSE 5-PHOSPHATE SYNTHASE; MEVALONIC ACID PATHWAY; ISOPRENOID BIOSYNTHESIS; CAROTENOID BIOSYNTHESIS; PEROXISOMAL LOCALIZATION; ARABIDOPSIS; EXPRESSION; CLONING; TRANSCRIPTION; PRECURSOR